Case report: Solitary fibrous tumor of the kidney with a NAB2-STAT6 fusion gene - Ji, Wen-Tong; Hu, Yu; Wang, Yao (Frontiers in Oncology, 2022)
We report a typical case of Solitary Fibrous Tumor (SFT). A 34-year-old woman presented to the urinary surgery department after physical examinations were suggestive of a urologic neoplasm. Further relevant imaging investigations suggested a renal tumor with benign behaviors. The patient was diagnosed with a kidney tumor suspected to be SFT and underwent laparoscopic radical left nephrectomy. Postoperative pathological immunohistochemical tests showed positivity for STAT6, CD-34, CD-99, and Bcl-2, thus confirming the diagnosis of SFT. Combined with the results of genetic testing of the patient, the tumor was indicated to carry NAB2: exon 6—STAT6: exon 16 mutation sites, which confirmed our diagnosis. The patient recovered quickly without any clinical evidence of incomplete resection. She has been followed-up for more than a year and will continue to be reviewed every three months to observe the final outcomes. Through this case, we analyzed the outcomes of imaging investigations and pathological examinations, and indicated potential areas for future research. We also creatively speculate on the molecular mechanism of SFT arising from the transcription process.